Boshlang‘Ich Sinflarda Ingliz Tilini O’qitish Metodikasi - Isanova Visola Oybekovna (Scholars Digest Publishing, 2023)
This article gives you a brief overview on how to teach English quickly and easily in elementary school. In this article, you can learn about meaningful and fun ways to teach English to children.
Keywords: elementary, English, children, teaching, fun, song, action, explanation, quick and easy, young children, mental, physical, teacher, voices.